Review of Dancing Parasites in Lymphatic Filariasis - Dietrich, Christoph F.; Chaubal, Nitin; Hoerauf, Achim; Kling, Kerstin; Piontek, Markus Schindler; Steffgen, Ludwig; Mand, Sabine; Dong, Yi (Ultrasound International Open, 2019)
Lymphatic filariasis is an infection transmitted by blood-sucking mosquitoes with filarial nematodes of the species Wuchereria bancrofti, Brugia malayi und B. timori. It is prevalent in tropical countries throughout the world, with more than 60 million people infected and more than 1 billion living in areas with the risk of transmission. Worm larvae with a length of less than 1 mm are transmitted by mosquitoes, develop in human lymphatic tissue to adult worms with a length of 7–10 cm, live in the human body for up to 10 years and produce millions of microfilariae, which can be transmitted further by mosquitoes. The adult worms can be easily observed by ultrasonography because of their size and fast movements (the so-called “filarial dance sign”), which can be differentiated from other movements (e. g., blood in venous vessels) by their characteristic movement profile in pulsed-wave Doppler mode. Therapeutic options include (combinations of) ivermectin, albendazole, diethylcarbamazine and doxycycline. The latter depletes endosymbiotic Wolbachia bacteria from the worms and thus sterilizes and later kills the adult worms (macrofilaricidal or adulticidal effect).
Keywords: parasite; guideline; elastography; contrast-enhanced ultrasound